Enhancing Learning Satisfaction in Technology-Driven Education: A Case Study from a Public University in Chongqing, China - Xuan, Guo (Scholar: Human Sciences, 2025)
Purpose: The study investigates the influence of five independent variables (Perceived Learning Effectiveness, Perceived Enjoyment, Perceived Usefulness, digital communities, and Information Technology) on the dependent variable (Students’ Learning Satisfaction). Research design, data, and methodology: The research employed the Index of Item-Objective Congruence (IOC) for validity and a Cronbach’s Alpha in a pilot test (n=30) for reliability. 80 valid responses from students at a Public University in Chongqing were analyzed by multiple linear regression to verify the significant relationship between variables. Following this, a group of 30 students underwent a 12-week strategic plan. Afterward, the quantitative results from the strategic and pre-strategic plans were analyzed in the paired-sample t-test for comparison. Results: In multiple linear regression, the study revealed that perceived learning effectiveness, perceived enjoyment, perceived usefulness, and information technology significantly impacted students’ learning satisfaction in Technology-enhanced learning. Finally, the results from the paired-sample t-test for comparison demonstrated significant differences in students’ learning satisfaction between the post-strategic and pre-strategic plans. Conclusion: The study revealed that the research conceptual model successfully predicted and explained perceived learning effectiveness, perceived enjoyment, perceived usefulness, and information technology emerged as crucial predictors and antecedents of learning satisfaction.